The Metacoupling Framework Informs Stream Salmonid Management and Governance - Carlson, Andrew K.; Taylor, William W.; Hughes, Sara M. (Frontiers in Environmental Science, 2020)
Stream salmonid fisheries are ecologically and socioeconomically important at local to global scales throughout the world. Although these fisheries are interacting systems of biota, habitats, and humans, systematic social-ecological integration across space and time is scarce. However, theoretical and methodological advancements in the study of coupled human and natural systems (CHANS) offer new insights for stream salmonid research, management, and policymaking. The metacoupling framework is a novel tool for studying and managing social-ecological linkages that occur within stream salmonid fisheries as well as between adjacent and distant fisheries (i.e., metacouplings). For instance, coldwater streams containing brook charr (Salvelinus fontinalis) and brown trout (Salmo trutta) in Michigan, USA, encompass metacoupled movements of water, information, fish, people, and money throughout CHANS that provide drinking water, recreational fisheries, and employment. However, groundwater withdrawal is altering stream hydrology and causing public controversy over how hydrological changes affect salmonid populations and thermal habitats. Using this complex social-ecological scenario as a case study, we describe the utility of the metacoupling framework for fisheries systems analysis and demonstrate how this approach promotes metacoupled governance—management of relationships among metacoupled systems rather than specific physical places alone—to better sustain stream salmonid fisheries locally, regionally, and globally. Overall, stream salmonid science and management can be enhanced by using the metacoupling framework to synthesize social and ecological information, characterize cross-scalar tradeoffs and feedbacks, understand stakeholder diversity, and ultimately develop metacoupling-informed policies that promote socially and ecologically desirable outcomes.